Reliability, Responsiveness, and Validity of the Visual Analog Fatigue Scale to Measure Exertion Fatigue in People with Chronic Stroke: A Preliminary Study - Benjamin Y. Tseng; Byron J. Gajewski; Patricia M. Kluding (Stroke Research and Treatment)
Background and Purpose. Post-Stroke Fatigue (PSF) is a prevalent yet commonly neglected issue that impacts daily functions and quality of life in people post-stroke. To date no studies have attempted to validate a clinically-feasible and reliable instrument to quantify PSF. We developed the Visual Analog Fatigue Scale (VAFS) to eliminate difficulties and poor data validity in testing people post-stroke. The purpose of this study was to evaluate the reliability, responsiveness, and validity of the VAFS. Methods. Twenty-one people post-stroke (12 males, age =59.5±10.3 years; time post-stroke =4.1±3.5 years) participated. Subjects underwent a standardized fatigue-inducing exercise; fatigue level was assessed at rest, immediately after exercise, and after recovery. The same protocol was repeated after 14 days. Results. ICC values for the VAFS at rest was 0.851 (CI = 95%, 0.673 ∼ 0.936, P<.001), immediately after exercise was 0.846 (CI = 95%, 0.663 ∼ 0.934, P<.001), and 15 minutes after exercise was 0.888 (CI = 95%, 0.749 ∼ 0.953, P<.001). The ES values for at-rest to post-exercise and for post-exercise to post-recovery were 14.512 and 0.685, respectively. Using paired t-test, significant difference was found between VAFS scores at-rest and post-exercise (P<.001), and between post-exercise and post-recovery (P<.001). Conclusion. Our data suggests good reliability, responsiveness, and validity of the VAFS to assess exertion fatigue in people post-stroke.